Determining a sourcing approach to infrastructure asset maintenance : a case study in the City of Cape Town: assessing the insourcing and outsourcing approach - Meyer, Ronel (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPA)--Stellenbosch University, 2022.